Społeczne konsekwencje podwyższenia wieku emerytalnego kobiet - Klimkiewicz, Aldona (Annales. Etyka w Życiu Gospodarczym, 2013)
The subject matter of the study is an analysis of the social consequences of increasing the retirement age of women up to 67 years. The discussion on the change in the retirement age is usually focused on its economic and financial aspects, hence a deeper scientific analysis is needed in relation to the social repercussions of this operation. The main subjects of the study are as follows: maintenance of equality tendencies in relation to the principles of social justice, changes in the social structure manifested especially on the labour market, social expectations as to employment security for those approaching retirement and development of flexible forms of working, development of incentives encouraging employers to keep current staff or hire new employees of older age, and changes in social roles.